1989
DOI: 10.1104/pp.91.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Starvation Inducible Metabolism in Lycopersicon esculentum

Abstract: Phosphate starvation increased the secretion of at least six proteins by suspension cultured tomato (Lycopersicon esculentum L. and L. pennellii) cells. Cells exhibited a biphasic response to phosphate (Pi) starvation. The early phase involved enhanced secretion of three proteins in response to transfer to a Pi-depleted media, while biomass accumulation continued at the same rate as in the Pi-sufficient cells. Severe starvation, defined as inhibition of biomass accumulation, induced enhanced secretion of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Likewise, the increase in Pi uptake rate by the AlF x -pretreated roots correlates well with the profile exhibited by Pi-starved roots ( Fig. 5; see also data from Clarkson and Scattergood, 1982;Goldstein et al, 1989) and is consistent with the time required for induction of phosphate transporter proteins in response to Pi starvation (Muchhal and Raghothama, 1999).…”
Section: Physiological Considerationsupporting
confidence: 74%
“…Likewise, the increase in Pi uptake rate by the AlF x -pretreated roots correlates well with the profile exhibited by Pi-starved roots ( Fig. 5; see also data from Clarkson and Scattergood, 1982;Goldstein et al, 1989) and is consistent with the time required for induction of phosphate transporter proteins in response to Pi starvation (Muchhal and Raghothama, 1999).…”
Section: Physiological Considerationsupporting
confidence: 74%
“…SDS-PAGE analyses have revealed that the CCF of +Pi, )Pi, and Pi-resupplied tomato suspension cells contain up to 50 different polypeptides, several of which are unique to )Pi cultures [20,24] (also this study, not shown). This suggests that the pair of Pi-inducible secreted serine protease isoforms of cultured tomato cells (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Inducible expression of P i transporters is vital for growth of plants under varying concentrations of P i . The induction of LePT1 protein in response to P i starvation correlates with the observed increase in P i uptake rate of roots and cell cultures (27,31). Addition of protein synthesis inhibitors suppressed P i starvation-induced P i uptake in tobacco cell cultures, indicating that de novo synthesis of P i transporters is required for the transport process (28).…”
Section: Discussionmentioning
confidence: 57%